The Role of Leaders in Promoting Creativity in the Workplace: An Examination of Individual and Organizational Antecedents in Innovation Management - Eric NEUENFELDT; Rozália SULÍKOVÁ (Communications of International Proceedings, 2024)
This study explores the pivotal role leaders play in fostering creativity and innovation within organizations. As businesses face rapidly evolving markets and technological advancements, the ability to remain competitive hinges on leveraging creativity and innovation. The study aims to elucidate how leadership can cultivate an environment conducive to creative thinking and innovative practices. While previous research has underscored the importance of creativity and innovation, there is a gap in understanding the specific mechanisms through which leaders influence these elements at both individual and organizational levels. This study addresses this void by providing a comprehensive analysis of the antecedents of creativity influenced by leadership. The study employs a qualitative approach, synthesizing existing literature and theoretical frameworks to examine the multifaceted role of leaders in promoting creativity and innovation. Key factors such as leadership styles, communication, support mechanisms, and organizational culture are analyzed to determine their impact on creativity. The research draws from a broad range of academic sources to build a cohesive narrative on the subject. The study finds that leaders significantly impact both individual and organizational antecedents of creativity. By fostering a culture of openness, risk-taking, and continuous improvement, leaders can inspire creative thinking and innovative solutions. Effective leadership involves providing resources, encouraging collaboration, and establishing psychological safety. The findings highlight that organizations prioritizing leadership development can unlock their teams' creative potential, driving innovation and maintaining a competitive edge in dynamic markets.
Keywords: Leadership; Creativity; Innovation; Organizational Culture; Innovation Management